Stochastic panel analysis of globalization and poverty reduction in BRICS countries: Implications for sustainable development - Johnson Ifeanyi Okoh; Wahid Damilola Olanipekunm; Timothy Ayomitunde Aderemi; Mamdouh Abdulaziz Saleh Al-Faryan (International Journal of Management, Economics and Social Sciences (IJMESS), 2022)
This study investigated dynamic interaction between globalization and poverty reduction in BRICS countries within the period of 1990 and 2019. This study is motivated by the rising development challenges confronting the world today, in which poverty reduction and the lack of empirical studies regarding globalization and poverty reduction in BRICS countries are significant. The study utilized the techniques of Impulse Response Functions (IRFs) and Variance Decomposition to address the objective of this study. The results from this study showed that a long-run convergence existed among globalization components and poverty reduction in BRICS countries. Also, FDI, trade openness and the number of people using internet, and HDI responded immediately to each other's policy shocks, but not in the most desired or best direction. Therefore, the policymakers and other relevant stakeholders in BRICS countries need to embark on swift policy responses that will shape and redirect the economic components of globalization- inflows of FDI, trade openness and the number of people using internet in such a way to bring poverty reduction in this economic bloc.
Keywords: F21; F23; F36; 330; Globalization; poverty; HDI; BRICS; SDGs